The Opportunities, Challenges, and Strategies in Adopting the Franchising Business Model: A Literature Review - Chhayna Cheng (Institut Teknologi dan Bisnis Asia Malang, 2026)
Despite research on the franchising business model has been growing, a comprehensive examination of its opportunities, challenges, and strategies remains insufficient. This study aims to bridge this gap in the existing literature by offering an in-depth analysis of these aspects within a unified dimension. This study employed a literature review method, integrated inclusion criteria, and used document analysis as its research approach. The study analyzed various documents, mainly scholarly works published between 2015 and 2025. By drawing on secondary data, this review demonstrates that franchising offers numerous opportunities for franchisees, such as existing brand awareness and recognition, support from the franchisor, and product or service innovations. However, it also highlights notable challenges, including legal, economic, and cross-cultural barriers, which can hinder the long-term success of franchising operations. Furthermore, this article emphasizes effective strategies used across different enterprises and sectors, such as franchisee characteristics, strategic management, marketing strategies, ethical standards, and technology adoption, all of which help maintain branding, growth, and resilience in a complex and competitive environment. Overall, this review suggests directions for future research to investigate franchise businesses across various industries and settings rigorously.